Removal of uterine polyps: clinical management and surgical approach. (3rd July 2020) - Ludwin, A.; Lindheim, S. R.; Booth, R.; Ludwin, I.
Abstract: Endometrial polyps have a reported prevalence from 7.8% up to 30% and are one of the most cost-consuming gynecological conditions for our specialty. There are strong practitioner beliefs that surgical removal of endometrial polyps is highly beneficial, particularly for those with abnormal uterine bleeding and infertility. Additionally, polypectomy is indicated to reduce the risk of malignancy. Transvaginal ultrasound is the first-line diagnostic option for detection of endometrial polyps, while sonohysterography has similar accuracy as hysteroscopy in the diagnostic confirmation. Blind dilatation and curettage is not recommended for polyp removal; rather, hysteroscopy in the operating room and office setting using small-diameter hysteroscopic equipment is the standard approach. This can be performed without anesthesia in most women. While hysteroscopy is an effective method for polypectomy with a low complication rate, it is unknown whether this is truly beneficial for reproductive-age women with infertility and prior assisted reproduction therapy. The risk of malignancy in women with postmenopausal bleeding justifies the necessity of polypectomy with histologic tissue examination. In asymptomatic women, the risk of malignancy is low, and there are no known benefits of polyp removal in the prevention of malignant transformation. Cost-effective studies remain to be done to provide us with the optimal approach to endometrial polyps including the management of asymptomatic and/or infertile women, ideal location including office-based or the operating room setting, complication prevention including intrauterine adhesions, and recurrence issues.